Inhibition of Notch1 promotes hedgehog signalling in a HES1-dependent manner in chondrocytes and exacerbates experimental osteoarthritis. Issue 11 (5th February 2016) - Lin, Neng-Yu; Distler, Alfiya; Beyer, Christian; Philipi-Schöbinger, Ariella; Breda, Silvia; Dees, Clara; Stock, Michael; Tomcik, Michal; Niemeier, Andreas; Dell'Accio, Francesco; Gelse, Kolja; Mattson, Mark P; et al.
Abstract : Objectives: Notch ligands and receptors have recently been shown to be differentially expressed in osteoarthritis (OA). We aim to further elucidate the functional role of Notch signalling in OA using Notch1 antisense transgenic (Notch1 AS) mice. Methods: Notch and hedgehog signalling were analysed by real-time PCR and immunohistochemistry. Notch-1 AS mice were employed as a model of impaired Notch signalling in vivo. Experimental OA was induced by destabilisation of the medial meniscus (DMM). The extent of cartilage destruction and osteophyte formation was analysed by safranin-O staining with subsequent assessment of the Osteoarthritis Research Society International (OARSI) and Mankin scores and µCT scanning. Collagen X staining was used as a marker of chondrocyte hypertrophy. The role of hairy/enhancer of split 1 (Hes-1) was investigated with knockdown and overexpression experiments. Results: Notch signalling was activated in human and murine OA with increased expression of Jagged1, Notch-1, accumulation of the Notch intracellular domain 1 and increased transcription of Hes-1. Notch1 AS mice showed exacerbated OA with increases in OARSI scores, osteophyte formation, increased subchondral bone plate density, collagen X and osteocalcin expression and elevated levels of Epas1 and ADAM-TS5 mRNA. Inhibition of the Notch pathway induced activation of hedgehog signalling with induction of Gli-1 and Gli-2 and increased transcription of hedgehog target genes. The regulatory effects of Notch signalling on Gli-expression were mimicked by Hes-1. Conclusions: Inhibition of Notch signalling activates hedgehog signalling, enhances chondrocyte hypertrophy and exacerbates experimental OA including osteophyte formation. These data suggest that the activation of the Notch pathway may limit aberrant hedgehog signalling in OA.